Le travail journalistique à l’heure de la rhétorique de la « bonne gouvernance des médias » - Mohamed Ali Elhaou (Communication)
This is a follow-up to a study published in 2015. Although it covers some of the same ground, it also develops new approaches to issues surrounding the promotion of investigative journalism and the ideologization of human rights in Tunisia. Drawing on semi-structured interviews, content analysis, and documentation on “media reform,” the article conceptualizes the journalism profession as practiced against a background of democratic transition.